(untitled) (Singapore, 1998)
This book contains comprehensive reviews and reprints on dynamical groups, spectrum generating algebras and spectrum supersymmetries, and their applications in atomic and molecular physics, nuclear physics, particle physics, and condensed matter physics. It is an important source for researchers as well as students who are doing courses on Quantum Mechanics and Advanced Quantum Mechanics.
Keywords: Quantum theory,Lý thuyết lượng tử,Tương đối (vật lý)